The local, the global and the industry common: the case of the video game industry. (19th July 2018) - Cohendet, Patrick; Grandadam, David; Mehouachi, Chahira; Simon, Laurent
Abstract: In this article, we attempt to show how the reconciliation of the international business and economic geography perspectives allows a more refined analysis of the interplay between current business dynamics and local/global spaces of knowledge creation, leading to innovation. Our aim is to develop a framework to highlight how in some specific clusters, local establishments of multinational enterprises can contribute, in cooperation with local actors, to the building of a common infrastructure of innovation to enhance both the quality of local resources and the power of attraction of a given localization. Drawing on the example of the video game industry as a flagship of creative industries, we aim to clarify in particular how an industry is locally and globally built, through the formation of common infrastructures of innovation in some core creative clusters.